2016
DOI: 10.1136/openhrt-2015-000374
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training characteristics in cardiac rehabilitation programmes: a cross-sectional survey of Australian practice

Abstract: IntroductionExercise training is a core component of cardiac rehabilitation (CR), however, little information exists regarding the specific exercise interventions currently provided for coronary heart disease in Australian practice. We aimed to analyse the current status of exercise-based CR services across Australia.DesignCross-sectional survey.MethodsAustralian sites offering exercise-based CR were identified from publically available directories. All sites were invited by email to participate in an online S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…The first aimed to describe the status of CR in Australia 50 . Findings indicated that the mean exercise session duration was 55 minutes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The first aimed to describe the status of CR in Australia 50 . Findings indicated that the mean exercise session duration was 55 minutes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Also interestingly, in some regions physiotherapists were a main part of the team (n=17 of 21 papers reporting staff composition, e.g., Australia, England, Scotland, Northern Ireland, Wales, Denmark, Italy, Portugal, Spain, Mexico, Bahrain, Egypt, Qatar, UAE and Canada; e.g., 24,61,66,92 ), whereas in others, exercise specialists were more common (i.e., exercise physiologists, kinesiologists; n=7 of 21 papers reporting staff composition; North America, China and the Middle East; e.g., 24,93 ). Whether this is a function of availability of training programs and hence staff to hire, reimbursement policies in the healthcare system, costs to programs, or other factors is unknown, as is the impact for patient outcomes (although there is no basis on which to assume different outcomes would be observed).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Phase II usually involves patients attending a hospital-based programme as an outpatient, weekly or twice weekly over a 6- to 12-week period,9,27 although flexible modes of service delivery have been used to cater for the requirements of a broader range of patients (see Such modes have included centre or home-based services, as well as telephone, mobile and internet-based services 3. Phase II programmes provide initial physical, psychological, and social assessments to facilitate return to everyday function, and education regarding cardiovascular disease risk factors, and exercise and lifestyle changes that may have long-term cardioprotective effects 3…”
Section: Management Continuitymentioning
confidence: 99%
“…In fact, in routine health care, intensity is often regulated by perceived exertion. In Australia, 80% of cardiac rehabilitation centers use the Borg-RPE, and only 19% use heart rate or the results of an exercise performance stress test (Abell, Glasziou, Briffa, & Hoffmann, 2016).…”
Section: Minimizing Health Risksmentioning
confidence: 99%